Periodesasi Masa Jabatan Anggota Legislatif dalam Perspektif Negara Demokrasi Konstitusional - Hulain Hulain; Markoni Markoni; Achmad Edi Subiyanto; Joko Widarto (Journal on Education, 2023)
Elections for members of the legislature (DPR, DPD and DPRD) based on the Election Law do not receive regulation in the 1945 Constitution regarding limits on the periodization of the term of office of legislative members, as the periodization of the term of office of the President and Vice President is limited to only two terms in the 1945 Constitution and so also with the position of Regional Head who is equally limited by the periodization of his term of office in the Law. An electoral system like this is a reflection of an unhealthy democracy, because democracy is only in plots by elite political parties who are always thirsty for power, which consequently shackles people's sovereignty to exercise their political rights and closes the faucet of constitutional democracy running consistently (constitutionality). as mandated in Article 1 paragraph (3) of the 1945 Constitution which stipulates law as a reference and commander-in-chief to implement people's sovereignty based on the constitution (constitutional democracy). This research was carried out using normative legal research methods, namely by studying the 1945 Constitution and various laws and regulations related to elections. From this research it was found that there was a legal vacuum in the 1945 Constitution, because it did not regulate the existence of limits on the periodization of the term of office of legislative members, giving rise to injustice between public positions in the legislature and public positions in the executive branch which were limited to the periodization of their term of office in the 1945 Constitution. the people as holders of sovereignty based on the constitution, then in the fifth amendment to the 1945 Constitution there must be regulation of the people's rights to submit bills to fill the legal vacuum that occurs.